CFD Simulation of Air Flow Motion for FPLG Gas Exchange Process - Kamarulbakhrin, Satria Kamarin Azrai (2018)
Gas exchange process is an important aspect of engineering for internal combustion engine discussion. Every cycle combustion process results in residue in the combustion chamber. With that, a proper balance ratio of new clean charge is necessary to obtain to meet the required power produce for every cycle of combustion, minimize exhaust gas recirculation with increasing scavenging effect. This project aims to demonstrate the difference of inlet configuration setup compared to current configuration that effects gas exchange process and exhaust gas recirculation (EGR). The engine used is Free Piston Linear Generator (FPLG) engine adopting uni-flow scavenging effect with compressible air inlet of 8 bar. This project is carried out using ANSYS CFD simulation in showing air flow pattern, strength of tumble, swirl and scavenging effect subjected by different inlet configuration. Inclination of inlet configuration manage to develop swirling air flow motion and increasing of inlet inclination increase the swirling strength. 60-degree inlet configuration have the highest swirling strength with the closest percentage of mass flow rate at outlet to inlet.